The effectiveness of position limits: Evidence from the foreign exchange futures markets - Chang, Ya-Kai; Chen, Yu-Lun; Chou, Robin K.; Gau, Yin-Feng (Journal of Banking & Finance, 2013)
This study considers the effects of the relative size of hedger and speculator open interests and the potential impact of implementing position limits on the price discovery process in both JPY–USD and EUR–USD futures markets. Hedging trading exerts a negative impact, regardless of its size, on price discovery in futures markets. Hedgers are less likely to be information motivated, so their trading uniformly delays the price discovery process. However, there is a positive and nonlinear impact of speculators’ trade size on price discovery, the contribution of which depends on the relative size of the speculative open interest. Contrary to conventional wisdom among regulators, speculative trading does not harm the market in terms of market efficiency; as long as the percentage of speculators’ open interest is below an endogenously determined threshold (approximately 20% for EUR–USD and 16.3% for JPY–USD), speculative trading even improves futures market efficiency.